2019
DOI: 10.1007/s42452-019-1111-2
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of polyvinyl alcohol–starch composites reinforced with pulp

Abstract: Herein, we have investigated the reinforcing potential of starch and cellulose pulp in a matrix of polyvinyl alcohol (PVA). Polyvinyl alcohol, starch, and pulp fibers having different compositions were constructed in order to achieve better reinforced composite films. Various techniques were utilized for extract the physical, mechanical as well as thermal properties. The magnitudes of tensile strength were reduced with rising of starch content in PVA. Tensile strength values of (PVA + starch) mixtures were enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…The tensile strength of the polymers demonstrated the following order: 31.83 MPa (PSG-Zn) > 29.12 MPa (PS–-CuZn) > 23.71 MPa (PSG–Cu) > 18.05 MPa (PSG). The tensile strength of the four polymer films was higher than the reported value for PVA at 6.3 MPa [ 15 ]. Thus, the polymers embedded with CuO and ZnO nanoparticles possessed better strength than PVA.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The tensile strength of the polymers demonstrated the following order: 31.83 MPa (PSG-Zn) > 29.12 MPa (PS–-CuZn) > 23.71 MPa (PSG–Cu) > 18.05 MPa (PSG). The tensile strength of the four polymer films was higher than the reported value for PVA at 6.3 MPa [ 15 ]. Thus, the polymers embedded with CuO and ZnO nanoparticles possessed better strength than PVA.…”
Section: Resultsmentioning
confidence: 59%
“…Natural polymers are frequently combined with nanoparticles or other synthetic polymers to widen their applications [ 10 ]. Blending PVA with biodegradable polymers such as starch may increase the degradability of the recalcitrant polymer while improving the mechanical properties [ 11 , 12 , 13 , 14 , 15 ]. PVA composite films with cellulose nanowhiskers and hemp protein have also been reported to improve the mechanical properties of PVA [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…These typical results apparently demonstrated that composites enhancing by cellulose nanofibril with various sizes could showcase significantly different properties as well. Moreover, polyvinyl alcohol (PVA), a water-soluble crystalline polymer, has extensive prospects in the fields of food packaging film materials, textile, artificial organs and medical gels biomedical fields, etc, which predominantly put down to its biodegradability, biocompatibility, excellent film-forming properties and gas barrier properties [ 39 , 40 , 41 ]. PVA is normally used composites to lower down the cost of product without any compromise or partial compromise with its properties and the hydrophilic composition, which consists of hydroxyl groups in the PVA structure, is well-linked with carbohydrates, creating significant agreement in composites [ 40 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Перспективность применения композитов на основе ПВС и полисахаридов (ПС) в качестве БРП отмечают отечественные и зарубежные исследователи [5][6][7][8][9][10][11]. В качестве наполнителей могут применяться любые полисахариды и их смеси, удовлетворяющие технологическим и потребительским требованиям [12].…”
Section: Introductionunclassified